(untitled) - Slack, Gordy (San Francisco, 2007)
tarred Review. Slack, the former editor of natural history magazine Pacific Discovery, has long covered clashes between scientists and creationists, and he knows both sides thoroughly-his own father, an experimental psychologist, took up creationism in the late 1990s, following a conversion to fundamentalist Christianity. In 2005, online magazine Salon assigned Slack to cover a federal court case in which a group of parents sued a Pennsylvania school board after it voted to include creationist material in high school science curricula. While Slack never hides his own convictions-firmly in support of evolution-he is staunchly even-handed throughout, giving all players the opportunity to represent themselves and their ideas. Everyone involved in the case-the presiding judge, the opposing teams of attorneys, the students and townspeople of Dover-come alive in Slack's economical yet revealing prose, and his history of both the contemporary creationist resurgence and the long-running philosophical debates behind it provide some much-needed perspective on modern American culture wars. In this must-read for anyone involved in education-from federal officials to local school board voters-Slack demonstrates in crisp, clear language how science and religion are not opposites, but different ways of thinking, each valuable for different purposes.
Keywords: Evolution (Biology),Intelligent design (Teleology),Sự tiến hóa (Sinh học),Thiết kế thông minh (Mục đích luận); Study and teaching,Law and legislation,Study and teaching,Law and legislation,Dạy và học,Luật và pháp luật,Dạy và học,Luật và pháp luật; Pennsylvania,Dover,Pennsylvania,Dover,Pennsylvania,Dover,Pennsylvania,Dover